Board of Commissioners Composition and Earnings Management: A Test of Gender as a Moderating Variable - Jonathan Budi Putra; Sansaloni Butar Butar (Jurnal Akuntansi Bisnis, 2023)
This study examines the effect of the board of commissioners’ composition on earnings management with gender as a moderating variable. Firm samples were selected from Indonesian public companies for 2019-2021. By applying the purposive sampling technique, a total of 1499 company observations are available for hypothesis testing. This study found that gender does not affect the relationship between board composition and earnings management. In addition, board size has a negative relationship with earnings management, and board independence is not associated with earnings management. The practical implications of this research are as follows: 1) Companies need to increase the number of commissioners to improve the control function. 3) OJK needs to revise the minimum proportion of independent commissioners from 30% to 50% or more to improve the control function of the board of commissioners.